Matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry: revolutionizing clinical laboratory diagnosis of mould infections. (12th December 2014) - Gautier, M.; Ranque, S.; Normand, A.‐C.; Becker, P.; Packeu, A.; Cassagne, C.; L'Ollivier, C.; Hendrickx, M.; Piarroux, R.; Roilides, E.
Abstract The clinical diagnosis of mould infections currently involves complex species identification based on morphological criteria, which is often prone to error. Employing an extensive mould species reference spectral library (up to 2832 reference spectra, corresponding to 708 strains from 347 species), we assessed the extent to which matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) enhanced the accuracy of species identification. MALDI‐TOF MS data were validated against morphology‐based and DNA sequence‐based results with 262 clinical isolates collected over a 4‐month period in 2013. The implementation of MALDI‐TOF MS resulted in a dramatic improvement in mould identification at the species level (from 78.2% to 98.1%) and a marked reduction in the misidentification rate (from 9.8% to 1.2%). We then compared the mould identification results obtained before (i.e. 2011) and after (i.e. 2013) the implementation of MALDI‐TOF MS in routine identification procedures, which showed an improvement from 64.57% to 100%. Reassessment of a set of isolates from 2011 with this procedure, including MALDI‐TOF MS, yielded an increase in species diversity from 16 to 42 species. Finally, application of this procedure during a 16‐month period (2012–2013) enabled the identification of 1094 of 1107 (98.8%) clinical mould isolates corresponding to 107 distinct species. MALDI‐TOF MS‐based mould species identification may soon challenge traditional techniques in the clinical laboratory, as patient prognosis is largely contingent on rapid and accurate diagnosis.